PENGENALAN PRODUK PADA RAK TOKO MENGGUNAKAN METODE YOU ONLY LOOK ONCE (YOLO) DAN COLOR HISTOGRAM - Kevin Kurniawan; Lina Lina (Jurnal Ilmu Komputer dan Sistem Informasi, 2021)
Basically, it is very easy for humans to detect and recognize the types of products that are in the supermarket on pictures or videos. For computers, the difficulty of recognizing and classifying a product is highly dependent on data. The lighting conditions, complexity, and background contrast of an image or video are one of the main challenges. In addition, the overall image or video quality is also very influential on the recognition results. Dairy products come in a variety of colors. Some models have several other products. The test results have a success rate of 72% for detection and a recognition success rate of 98% for dairy products.